The Relationship Between the Reputation of the Sports Team Perceived by University Students and Their Psychological Commitments to Their Teams - Ramazan Sanlav,; Pero Duygu Dumangöz, (Journal of Educational Issues, 2024)
This study aims to examine the relationship between the reputation of sports team perceived by university students and their psychological commitment to their teams and to determine whether these two variables differ according to variables such as gender, age, department of university, the status of membership to a fan union, and the team the students supported. This is a quantitative study utilizing descriptive scanning model. The population of the study consists of students studying in universities on the European Side of Istanbul, and the sample consists of 219 students contacted by the random selection method. The study applied personal information form prepared by the researcher, the Spectator-Based Sports Team Reputation Scale (SSTR), which was developed by Wonseok et al. (2015) and the Fan Psychological Commitment Scale (FPCS), which was developed by Matsuoka (2001) in order to collect data in the study. SPSS 20.0 software package was used for data analysis. The collected data were examined with Kolmogorov-Smirnov and distribution graphs in terms of normal distribution in addition to descriptive statistics. Mann-Whitney U and Kruskal-Wallis tests were used to compare the data based on the number of variables. Post-hoc analyses were conducted by Mann-Whitney U test using Bonferroni correction and relationships between variables by Spearman’s correlation analysis. The prediction of the FPCS score by SSTR score was evaluated through linear regression analysis. The error margin was accepted as p < 0.05. A positive significant relationship was found between FPCS and SSTR variables perceived by university students according to the research results (p < 0.05). The results have strategic implications for managers who can evaluate the team reputation and the psychological commitment of the fan to the team in this context and encourage this for more fan participation.